Exercise training elicits superior metabolic effects when performed in the afternoon compared to morning in metabolically compromised humans. Issue 24 (23rd December 2020) - Mancilla, Rodrigo; Brouwers, Bram; Schrauwen‐Hinderling, Vera B.; Hesselink, Matthijs K. C.; Hoeks, Joris; Schrauwen, Patrick
Abstract: The circadian clock and metabolism are tightly intertwined. Hence, the specific timing of interventions that target metabolic changes may affect their efficacy. Here we retrospectively compared the metabolic health effects of morning versus afternoon exercise training in metabolically compromised subjects enrolled in a 12‐week exercise training program. Thirty‐two adult males (58 ± 7 yrs) at risk for or diagnosed with type 2 diabetes performed 12 weeks of supervised exercise training either in the morning (8.00–10.00 a.m., N = 12) or in the afternoon (3.00–6.00 p.m., N = 20). Compared to participants who trained in the morning, participants who trained in the afternoon experienced superior beneficial effects of exercise training on peripheral insulin sensitivity (+5.2 ± 6.4 vs. −0.5 ± 5.4 μmol/min/kgFFM, p = .03), insulin‐mediated suppression of adipose tissue lipolysis (−4.5 ± 13.7% vs. +5.9 ± 11%, p = .04), fasting plasma glucose levels (−0.3 ± 1.0 vs. +0.5 ± 0.8 mmol/l, p = .02), exercise performance (+0.40 ± 0.2 vs. +0.2 ± 0.1 W/kg, p = .05) and fat mass (−1.2 ± 1.3 vs. −0.2 ± 1.0 kg, p = .03). In addition, exercise training in the afternoon also tended to elicit superior effects on basal hepatic glucose output ( p = .057). Our findings suggest that metabolically compromised subjects may reap more pronounced metabolic benefits from exercise training when this training is performed in the afternoon versus morning. ClinicalTrials.gov ID: NCT01317576. Abstract : Afternoon exercise is more optimal than morning to improve insulin sensitivity, body composition, and exercise performance in metabolically compromised individuals.